Interactive Teachable Cognitive Agents: Smart Building Blocks for Multiagent Systems - Subagdja, Budhitama (2016)
Developing a complex intelligent system by abstracting their behaviors, functionalities, and reasoning mechanisms can be tedious and time consuming. In this paper, we present a framework for developing an application or software system based on smart autonomous components that collaborate with the developer or user to realize the entire system. Inspired by teachable approaches and programming-by-demonstration methods in robotics and end-user development, we treat intelligent agents as teachable components that make up the system to be built. Each agent serves different functionalities and may have prebuilt operations to accomplish its own design objectives. However, each agent may also be equipped with in-built social-cognitive traits to interact with the user or other agents in order to adapt its own operations, objectives, and relationships with others. The results of adaptation can be in the form of groups or multiagent systems as new aggregated components. This approach is made to tackle the difficulties in completely programming the entire system by allowing the user to teach the components toward the desired behaviors in the situated context of the application. We exemplify this novel method with cases in the domains of human-like agents in virtual environment and agents for in-house caregiving.